Social movements and public policies - action of the NGO HTLVida - Silva, Ionara de Oliveira Garcia; Hennington, Élida Azevedo (Saúde e Sociedade, 2023)
In contemporary history, several forms of civil society organizations have stood out in the struggle to expand rights. Non-governmental organizations dedicate themselves to extending the rights of the group for which they were created. This study shows the work of the HTLVida to NGO introduce HTLV to the governmental agenda of Bahia State, Brazil, and to extend rights for this population. HTLV is a retrovirus affecting T lymphocytes which can cause neurological and hematological diseases, among others. Brazil has the highest absolute number of cases and Bahia is one of the states with the highest infection prevalence. We found that several factors contributed to including the topic in the Bahia government agenda and the subsequent implementation of rights; among these, the strong militancy of individuals infected with the virus in the HTLVida group. Regarding their achievements, we highlight the structuring of a municipal outpatient clinic, the creation of the Municipal Day to Confront HTLV, and its inclusion in activities related to STIs in health departments. Despite significant advances, this social movement still needs to persist to mobilize the expansion of social rights for people living with HTLV.